FREQUENCY OF PROTHROMBIN GENE MUTATION IN VENOUS THROMBOEMBOLISM IN NORTHERN PAKISTAN - Sajjad, Dr Zunera; Khan, Saleem Ahmed; Malik, Hamid Saeed; Altaf, Chaudry; Khan, Nabeela; Khurshid, Ayesha (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the frequency of prothrombin gene mutation in venous thromboembolism in ourpopulation.Study Design: Cross sectional study.Place and Duration of Study: Department of Haematology, Armed Forces Institute of Pathology Rawalpindi,from Jun 2015 to Dec 2016.Material and Methods: This cross sectional study was conducted in the Department of Haematology, ArmedForces Institute of Pathology Rawalpindi from Jun 2015 to Dec 2016. This study involved patients of both gendersaged between 15-45 years who presented with one or more episodes of deep vein thrombosis or pulmonaryembolism. Outcome variable was frequency of prothrombin gene mutation which was assessed by PCR ofgenomic DNA.Results: A total of 96 newly diagnosed patients of venous thromboembolism were analyzed. Out of these, 79patients had deep vein thrombosis and 17 had pulmonary embolism. Prothrombin gene mutation was seen in 4(4.2%) patients. The frequency of prothrombin gene mutation was significantly higher among patients withpulmonary embolism (p=0.002) and recurrent episodes (p=0.046).Conclusion: The frequency of prothrombin gene mutation was found to be 4.2% in the present study. It wassignificantly higher in patients with pulmonary embolism and recurrent thrombosis.